Exopolysaccharide Production from Six Different S. boulardii Strains and Determination of Monosaccharide Composition, Rheological and Antioxidant Properties - Goktas, Hamza; Agan, Cansu; Bekiroglu, Hatice; Bozkurt, Fatıh (My University, 2025)
Yeast derived EPSs have gained much popularity due to their techno-functional properties in recent years. In this context, six different S. boulardii strains, proven for their probiotic properties, were used to obtain EPS. HPLC results showed that the Sb EPSs had the heteropolysaccharide structure, and were mainly composed of mannose and glucose units. Besides this, fructose (only detected in S3 and S6), rhamnose (S4, S6, S7, S8, and S9) and galactose (S3, S6, S7, S8, and S9) were detected. However, xylose was not detected in any Sb EPS samples. FT-IR results confirmed the polysaccharide structure of Sb EPSs. The Sb EPSs exhibited more than 100% water holding capacity, and high-water solubility index. Within this context, the WHC and WSI values for the Sb EPSs ranged from 104.02±1.40 % to 102.38±0.89 % and 89.41±0.71 % to 82.14±6.60 %, respectively. The Sb EPSs exhibited shear thinning flow behaviour, and their viscosities were lower than those of guar gum. The Sb EPSs had excellent antioxidant activity for all tested three antioxidant methods of ABTS, DPPH, and FRAP. Accordingly, the antioxidant activities for the Sb EPSs, determined by the DPPH, ABTS, and FRAP assays, were found to be in the ranges of 53.59±0.29% (S6) to 49.25±0.44% (S9); 84.71±0.64% (S3) to 69.08±1.99% (S7); and is 121.33±2.20 (S6) to 97.16±3.33 (S9) mg TE/100 g, respectively. Especially the S6 EPS sample displayed high antioxidant activity in all three methods (P?0.05). These results showed that Sb EPSs may be a good alternative in food applications.
Keywords: Rheology; Exopolysaccharide; S. Boulardii; Hplc; Ft-Ir